Acute Viral Hepatitis E Is Associated with the Development of Myocarditis - M. Premkumar; Devraja Rangegowda; Chitranshu Vashishtha; Vikram Bhatia; Jelen Singh Khumuckham; Badal Kumar (Case Reports in Hepatology)
Myocarditis, an inflammatory disease of heart muscle, is an important cause of dilated cardiomyopathy worldwide. Viral infection is an important cause of myocarditis. This condition presents with various symptoms, ranging from minimally symptomatic cases to fatal arrhythmia and cardiogenic shock, and may develop chronic myocarditis and dilated cardiomyopathy in some patients. We report the case of a 26-year-old patient with acute viral hepatitis E who developed symptomatic myocarditis. As far as we could search, this is probably the 3rd case report of this rare association.